Non-indigenous cephalopods in the Mediterranean Sea : a review - Bello, Giambattista (Array, 2020)
The present review critically assesses the records of cephalopods that have entered the Mediterranean Sea in the last few decades. It includes 13 species, namely Sepia dollfusi, Stoloteuthis leucoptera, Sepioteuthis lessoniana, Architeuthis dux, Cranchia scabra, Taonius pavo, Megalocranchia sp., Teuthowenia megalops, Cycloteuthis sirventi, Taningia danae, Octopus cyanea, Amphioctopus sp. and Tremoctopus gracilis. The presence of Sepia pharaonis needs to be confirmed, whereas that of Sepia gibba and Spirula spirula is excluded. The arrivals from the Atlantic Ocean through the Strait of Gibraltar are related to the entrance surface current, which either carried passively planktonic paralarvae or favoured in some other way the entrance of subadult and adult stray specimens. As a matter of fact, all Atlantic cephalopods are pelagic oegopsid squids, with the exception of the nekto-benthic sepiolid S. leucoptera; all of them have been found only in the western Mediterranean basin. None of them seemingly established a stable population there, apart from the latter species. On the contrary, the cephalopods entering the Mediterranean from the Red Sea through the Suez Canal (Lessepsian migrants) lead a benthic mode of life. At least two of them, namely S. lessoniana and Amphioctopus sp., set up stable populations in the eastern basin. Lastly the occurrences of the pelagic octopod T. gracilis are ascribed, in the literature, to human-mediated transfer.